EVALUATION OF CURRENT PRESCRIBING PRACTICES – A METHOD TO REDUCE THE COST OF THERAPY (Journal of Pharmaceutical Negative Results, 2022)
In India, there are more chances of the diseases in the poor, who are unaware of hygiene and it is very difficult for them to afford the treatment. The escalating costs of prescription drugs have become a substantial economic burden on patients with limited income. Since a large number of people in developing countries are economically challenged, many of them cannot afford required treatment. We need to ensure that the poor and vulnerable are not priced out of access to the medications they need to keep them out of the hospital, and to ensure a good quality of life. Any method which decreases the cost of therapy can be boon for the poor and the vulnerable. There are different brands of a single drug available in the market with different prices. But these drugs that are marketed under different brand names are similar in nature ( i.e, they are similar in API , dose and form ). So, the present study was based on the comparison of prices of different brands of extensively used drugs in the health care system which are employed for chronic or acute usage for decreasing the mortality and the morbidity of the patients. Results have shown that in the current scenario, upto 99.72% cost could be saved by substituting the highest priced brand with the lowest priced brand in a prescription. Hence , it is possible for a physician to decrease the cost of therapy especially of poor patients by comparing the prices of different brands of drugs & prescribing the low priced brands.